PENGARUH BRAND IMAGE, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI DI AR STORE PADANG - Putri, Yorie Nadila; Rahmadanirwati, Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This research aims to determine the effect of brand image, price, and promotion on purchasing decisions for Xiaomi smartphones at AR Store Padang. The method used in this research was a survey with a questionnaire, which involved 90 respondents as samples using a non-probability sampling technique with a saturated sampling type, where the entire sample population was used. Data analysis techniques include validity, reliability, classical assumption tests, and multiple linear regression analysis to see the influence of brand image, price, and promotion on consumer purchasing decisions. The research results show that brand image, price, and promotion positively and significantly influence the decisions to purchase a Xiaomi smartphones at the AR Store Padang.Keywords: Brand Image, Price, Promotion and Purchasing Decisions